Molecular Modification of Levan and Biotechnological Applications of its Derivatives - (:unkn) unknown (CAISTER ACADEMIC PRESS, 2019)
Levan is a fructose-based homopolymer, a fructan, with emerging potential in different fields, including biotechnology, food and health. It is obtained from sucrose by a wide range of microorganisms. Levan has become a versatile biopolymer due to its physicochemical and biological properties stemming from its molecular weight, functional groups and degree of substitution. Levan can undergo changes in its molecular structure to broaden its functional properties and consequently its applications. Molecular modification methods mainly involve chemical, physical and biological changes. Chemical modification is the most widely used method to enhance the bioactivity of levan, which occurs through the addition or substitution of functional groups. Physical and biological modifications alter only the molecular weight into varied sizes. This review offers a description of the main molecular modification methods of levan and the contributions to its physicochemical and biological properties.
Keywords: ZYMOMONAS-MOBILIS; IN-VITRO; ANTIOXIDANT ACTIVITIES; HALOMONAS-SMYRNENSIS; ANTITUMOR-ACTIVITY; MULTILAYER FILMS; SULFATED LEVAN; LEVANSUCRASE; FRUCTOOLIGOSACCHARIDES; OLIGOSACCHARIDES